2020
DOI: 10.1016/j.bbrc.2020.04.136
|View full text |Cite|
|
Sign up to set email alerts
|

Biochemical characterization of SARS-CoV-2 nucleocapsid protein

Abstract: The nucleocapsid (N) protein is an important antigen for coronavirus, which participate in RNA package and virus particle release. In this study, we expressed the N protein of SARS-CoV-2 and characterized its biochemical properties. Static light scattering, size exclusive chromatography, and small-angle X-ray scattering (SAXS) showed that the purified N protein is largely a dimer in solution. CD spectra showed that it has a high percentage of disordered region at room temperature while it was best structured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
426
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(491 citation statements)
references
References 31 publications
41
426
0
5
Order By: Relevance
“…expressed during infection 155,156 . N binds viral RNA through both its Nand C-terminal domains, connected by a disordered SR-rich linkage region 157,158 . Of note, given its high abundance within the viral particle, N is the first viral protein released in the host, prior to viral RNA translation.…”
Section: Nsp14 Associates With Rna Decapping and Deadenylation Host Fmentioning
confidence: 99%
“…expressed during infection 155,156 . N binds viral RNA through both its Nand C-terminal domains, connected by a disordered SR-rich linkage region 157,158 . Of note, given its high abundance within the viral particle, N is the first viral protein released in the host, prior to viral RNA translation.…”
Section: Nsp14 Associates With Rna Decapping and Deadenylation Host Fmentioning
confidence: 99%
“…This is in agreement with other studies that used slightly different sequences/alignments. [34][35] The N protein sequence of MERS-CoV shares only 42% to 44% similarity with the SARS-CoV-1 and SARS-CoV-2 N protein, respectively.…”
Section: Phosphorylation On Nucleocapsid Proteinmentioning
confidence: 99%
“…6 Early studies, including recent review articles about the N protein, suggested that the N protein is a phosphoprotein and does not bear glycans on its backbone. 24…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a significant percentage of those infected are asymptomatic, with studies finding that 20% to over 40% of cases show no symptoms [2][3][4] , a condition that helps the silent spread of the disease. SARS-CoV-2 is an enveloped virus with a nucleocapsid made up of single-stranded RNA bound to protein N (Nucleocapsid), surrounded by a lipid membrane that contains structural proteins M (Membrane), E (Envelop) and S (Spike) [5][6][7][8] . The structure of protein S gives the virus its distinctive crown of spikes and is responsible for binding to the angiotensin-converting enzyme 2 (ACE2) receptor, which allows the virus to enter the host cell 9,10 .…”
Section: Introductionmentioning
confidence: 99%